If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(6c + -1) + -14 = 52c + 9 Reorder the terms: 9(-1 + 6c) + -14 = 52c + 9 (-1 * 9 + 6c * 9) + -14 = 52c + 9 (-9 + 54c) + -14 = 52c + 9 Reorder the terms: -9 + -14 + 54c = 52c + 9 Combine like terms: -9 + -14 = -23 -23 + 54c = 52c + 9 Reorder the terms: -23 + 54c = 9 + 52c Solving -23 + 54c = 9 + 52c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-52c' to each side of the equation. -23 + 54c + -52c = 9 + 52c + -52c Combine like terms: 54c + -52c = 2c -23 + 2c = 9 + 52c + -52c Combine like terms: 52c + -52c = 0 -23 + 2c = 9 + 0 -23 + 2c = 9 Add '23' to each side of the equation. -23 + 23 + 2c = 9 + 23 Combine like terms: -23 + 23 = 0 0 + 2c = 9 + 23 2c = 9 + 23 Combine like terms: 9 + 23 = 32 2c = 32 Divide each side by '2'. c = 16 Simplifying c = 16
| 9(3x+6)=(x-2) | | 52x^2+5x-100=0 | | 5(y-2)=2y-31 | | 20(c+-50)=19000 | | 2-5x=18+3x | | 9x+8=7x+36 | | (10)=2x-6 | | x=3x+16 | | 3y=48+18ty | | 288t-48t^2=0 | | 3x-2=5-4x | | 3y-3=13y+47 | | 3y-3=13+47 | | 3a=11 | | 5(k-7)-k+1= | | 5y-3=13y+47 | | -2y-12=5y+2 | | 12x+8x=7x+43 | | 8x-(5x-3)=12 | | 5(8-5b)-6(4-3b)=16 | | 2a+b=0 | | -2(6-x)+4=6-4(x+2) | | 12-8x=104-36x | | 187-6x=-6x+19 | | 3(x-11)=18-2(z-2) | | 12x+7=4(3x-2) | | |2x+1|=|x+5| | | -4c+3=-9 | | 12x^2-108x=o | | (x/1200)/(-300/2800)=1,2 | | 6x+3(3-x)=9 | | b+(-28)=-9 |